Bryonia dioica, Tamus communis and Lonicera periclymenum fruits: characterization in phenolic compounds and incorporation of their extracts in hydrogel formulations for topical application - Barreira, João C.M. (2013)
Plants are being increasingly used in dermatological formulations, since their collateral effects are lower than those caused by synthetic products. Hydrogels represent efficient formulations to incorporate plant extracts, providing good percutaneous absorption, non-greasy texture and easy application. Bryonia dioica Jacq. (white-bryony), Tamus communis L. (black-bryony) and Lonicera periclymenum L. (honeysuckle) fruits have important applications as topical homemade remedies. The phenolic extracts of B. dioica, T. communis and L. periclymenum were characterized by HPLC-DAD-ESI/MS, and further incorporated into hydrosoluble gels in order to evaluate their antioxidant potential. The hydrogels were prepared with each fruit extract at the EC50 value (obtained herein for each ethanolic extract). The antioxidant activity of extracts and hydrogels was evaluated following different chemical and biochemical assays. Eighteen compounds were identified in honeysuckle (7 flavonols, 7 hydroxycinnamoyl derivatives and 4 anthocyanins), fourteen in white-bryony (9 flavonols and 5 flavones) and twelve in black-bryony (7 flavonols and 5 flavones). Honeysuckle showed the highest concentrations of phenolic compounds, but the antioxidant activity was similar among the three assayed species. The obtained formulations revealed antioxidant activity close to 50% for reducing power, scavenging activity and β-carotene/linoleate assays. The studied fruits might be considered as good source of phenolic compounds that can be used in formulations for topical application, benefiting their antioxidant effects.